FENOMENA KESEJAHTERAAN BURUH/KARYAWAN PERUSAHAAN DI INDONESIA - Andri Novius (STIE Pelita Nusantara Semarang, 2007)
This study discuss about employee/laborer's benefit in Indonesian corporates. It's difficult for the employee to make their prosperous increased by themselves. It may effect to their dissatisfaction and caused in arising instability in social and economic. Competent authorities must solve this problem to avoid for future risk. It conduce not only to the laborer, but on the other side of it, for the corporate and the country too. Laborer needs attention for their viability immediately.